THREAD TENSION STABILIZING OF THE DEVICE ELASTIC ELEMENT PERMANENT POWER UNDER THE INFLUENCE CHARACTERISTICS EXPERIMENTAL ANALYSIS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Textile in the industry thread again wrapping in the process thread tension stabilizing of devices elastic element that is springs characteristics research TW2 - D machines at Artsoft Holding​ in the example of of springs singleness coefficients experimental determined. Research as a result spring up to 32–33% of virginity was unevenness of the bobbins mass and density various to be main reason that proven. The spring time to pass with elasticity properties decrease analysis made.